RESEARCH STRENGTH AND MICROSTRUCTURE MODIFIED PROTECTIVE AND DECORATIVE ACRYLIC COATING (Municipal economy of cities. Series: «Economy science», 2013)
The results of the research of adhesive strength compositions of protective and decorative coatings on the basis of acrylic dispersions modified by additives are presented. The analysis of the microstructure of the samples of the studied coatings is considered.